ANALISIS PENDAPATAN PEMBESARAN BEBEK PEDAGING DI DESA SUMBER JAYA KECAMATAN BELITANG II KABUPATEN OKU TIMUR - Muridin (Jurnal Bakti Agribisnis, 2018)
Muridin. 2017. To increase livestock development, the current development approach is through the development of livestock-based agribusiness areas. Currently in East OKU Regency there are a lot of food stalls (tent stalls) on the side of the road, the market sells food made from duck meat (fried duck), so it is necessary to provide duck meat ingredients that are raised by the community. Based on the description above, the researcher is interested in carrying out research on "Analysis of Rearing Broiler Ducks in Sumber Jaya Village, Belitang II District, East OKU Regency". Because many sources of jaya keep these broiler ducks. Based on the results of the study, it was found that the amount of production costs in raising broiler ducks was started from the depreciation of the equipment, the rental place, which was an average of Rp. 1,342,856 / production. The revenue obtained from the sales of broiler ducks is reduced by production costs, which is an average of Rp. 14,027,933 / month, while the average income in raising ducklings is Rp. 8,353,911 / month and the BEP price in raising broilers is Rp. IDR 17,446 in one production process.